Local Wisdom in Efforts to Preserve the Tubang Tubang Tradition Through Rejung Art - Fadhilah, Ayuni; Wardiah, Dessy; Hera, Treny (CV. Rayyan Dwi Bharata, 2024)
The research aims to analyze local wisdom in an effort to preserve the wai Tubang tradition through Rejung art in Ulu Danau Village, Sindang Danau South OKU District. What is meant is that local wisdom is considered a way of life in the form of knowledge that is formed from the activities of the community and is considered capable of overcoming existing needs. The method in this research uses descriptive qualitative research methods. This type of research describes events obtained that are both natural and human engineering. However, it is still based on characteristics, as well as the quality of relationships between activities. In connection with the focus of the problem seen from the existence of local wisdom in efforts to preserve the AWAT Tubang tradition through Rejung art, the researcher decided to use an ethnographic method. Spardley explained this method as a form of research method that pays attention to the meaning of actions in an event so that it is easy to understand.